Estudio de adaptación de siete pastos y tres mezclas forrajeras con la utilización de lactofermento en la comunidad de San Isidro, Parroquia La Matriz, Cantón Pujilí, Provincia De Cotopaxi 2019-2020. - Jessenia Carolina, Amores Carua (2020)
This research was carried out in the community of San Isidro, located in La Matríz Parish, Pujilí Canton, Cotopaxi Province with the coordinates: latitude South: 754890, longitude West: -9887823 at an altitude of 2900 meters, the objective was to determine which grass has the best adaptability at the sector. Seven different kinds of grass and three fodder mixtures were used, with the application of enriched lactoferment, using an experimental design of divided plots (A x B) obtaining twenty treatments and three repetitions where the following variables were analyzed: plant height, cover, microorganisms, and soil fungi. The pasture with the best agronomic behavior is the T4 (Ryegrass) treatment with a height of 71.42 cm at 57 days, while at 64 days the result was reflected in the T4 (Ryegrass) treatment with a height of 77.05 cm, while the pasture with the highest percentage of coverage at 57 days was the T4 (Ryegrass) treatment with a percentage of 91.17. So, it can be determined that the lactoferment did act in a representative way between the treatments and soil fertility. The microbiological analysis of the soil shows that the pastures of San Isidro from Pujilí, the treatment "T1" ("Pasto Azul") with 690 (UFC/g) obtained the best results in the count of yeasts present in the soil. In contrast, for the count of fungi, in the same way, the treatment "T1" ("Pasto Azul") obtained the best result with 35 (UFC/g). The results obtained from the biological composition of the lactoferment did not reveal the existence of microorganisms; while the chemical analysis revealed the presence of macro elements such as N (0.002g/100ml), P (0.03g/100ml), K (1.19g/100ml) and microelements such as B (0.31ppm), Zn (4074ppm), Cu (1.16 ppm) which are indispensable for the soil and therefore for the development of the pastures.